Perancangan User Interface dan User Experience Berbasis Website Sistem Pembayaran SPP Menggunakan Human Centered Design (Studi Kasus : SMAS Bhinneka Karawang) - Nurhidayah, Novi Anthika Suci; Nugraha, Bagja; ., Hannie (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
This research discusses the inefficiencies of the manual payment method at SMAS Bhinneka Karawang and emphasizes that the online payment system should be more accessible to parents to make the payment process easier. The main objective of this study is to create an easy to use tuition payment system for parents, school operators and foundation operators. Human Centered Design is the research methodology used to ensure that the system is tailored to the needs of the users. The results show that the design of the tuition payment system prototype significantly improved the payment process, with users stating that it was easy to use and had a 100% transaction success rate. Future research should concentrate on incorporating additional features, such as mobile payment capabilities and further analysis of user experience.